Composition and characteristics of the avifauna of the town of Kičevo (North Macedonia) - Joleski, Bojan (Macedonian Journal of Ecology and Environment, 2023)
In this paper I present an analysis of the avifauna of the town of Kičevo. The ornithological investigations were carried during a three years period, from January 2020 to February 2023. The qualitative investigations showed presence of 88 species of birds. They belong to 67 genera, 37 families and 13 orders. The most representative order is Passeriformes, with 14 families (62.2%) and 60 species (68.2%). The richest with species are the families Muscicapidae, Fringillidae, Corvidae and Paridae. The breeding avifauna is represented by 47 species (53.4 %). According to the seasonal status, the most numerous are residents (STAT) with 37 species (42.1%), then summer visitors (AEST) with 18 species (20.4%). Wintering (HIEM), transient (TRANS), and vagrant (VAG) species follow. The faunistic analysis show the domination of Palearctic (PA) type of fauna before the European (Ev) and European-Turkestanic (ET) type among the total avifauna, as they also do in the single groups by seasonal status. Comparing qualitative composition of the avifauna of Kičevo with Skopje and Đakovo, showed a low index of similarity 0.55 and 0.50 respectively, which is due to: geographical position, level of urbanization, coverage of green areas, position along important migratory routes, presence of water bodies and orography.